THE EFFECT OF RATIONS SUPPLEMENTED WITH A MIXTURE OF LYSINE, METHIONINE AND CHOLINE ON BALI BOAR PERFORMANCES - N. N., Sulastri; Sumadi, I K.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2018)
The research aim to determine the effect of rations supplemented with a mixture of lysine, methionine and choline on bali boar performances. This research was conducted for 12 weeks at Banjar Batu Paras, Padangsambian Kaja Village, West Denpasar. The design used was a complete randomized design (RAL) consisted of 3 treatments and 4 replications. The treatments of this research were ration without supplementation (T 0 ), ration with 0,5% mixture of lysine, methionine and choline supplementation (T 1 ) and ration with 1% mixture of lysine, methionine and choline supplementation (T 2 ). The variables observed were final weight, weight gain, feed consumption and feed conversion ratio. The results obtained will be analyzed using analysis of variance and if there is a significant difference (P<0.05) between treatments it was proceeded with Duncan multiple range test. The results showed that rationing with lysine, metionine and choline mixture supplementation of 0,5% (T 1 ) and 1% (T 1 ) in bali boar had significant effect on final body weight, weight gain, feed consumption and feed coversion ratio. Based on the results of this study concluded that the best results obtained from the supplementation of 1% mixture of lysine, metionine and choline in the ration of bali boar to final weight, weight gain, feed consumption and feed conversion ratio. Keywords: supplementation, bali boar , lysine, methionine, choline.